Factors of Developing International Retail Chain Brands in the Regions of the Russian Federation - Anna Mikhailovna Chernysheva; Alexandra Alexandrovna Trofimova; Valentina Viktorovna Kalygina; Mariya Andreyevna Bulatenko (Space and Culture, India, 2019)
The development of international and local (federal) retail chains is significant for the development of the country's economy in the modern context. It can be stated that the problems of the retail chain development are reviewed in applied aspects more successfully than in theoretical aspects, which reinforces their urgency. This article is devoted to the factors of international retail chain development in Russia by regions, including Moscow and St. Petersburg. The authors cite the development of outlet centres in the Russian regions and the quality of retail space as factors with a considerably e influence on the international retail chain development. The developers' task is to intensively develop the construction of outlet centres in cities with a million-plus population, ensuring that retail chains, primarily international ones, become anchor tenants. The reason is that anchor tenants become centres of attraction that provide rental of retail space (usually from 5% to 15% of the total area of the outlet centre) and offer a wide range of goods to the outlet centre visitors at attractive prices. The purpose of this article is to study the factors of international retail chain brand development in the regions of the Russian Federation and to establish a connection between the opening of outlet centres and the development of global retail chains. To this end, the statistical data presented in the JLL 2015 Report and official statements of authorised representatives and agencies regarding the development of retail chains were analysed. It is suggested that a close relationship between the opening of outlet centres and the development of international retail chains in the regions of the Russian Federation will be established during the analysis, including the classification of cities for the development of global retail chains due to the effect of various factors.